Differential interaction of NMDA receptor subtypes with the post-synaptic density-95 family of membrane associated guanylate kinase proteins. - Cousins, S; Papadakis, M; Rutter, A; Stephenson, F (2008)
NMDA receptors are a subclass of ionotropic glutamate receptors. They are trafficked and/or clustered at synapses by the post-synaptic density (PSD)-95 membrane associated guanylate kinase (MAGUK) family of scaffolding proteins that associate with NMDA receptor NR2 subunits via their C-terminal glutamate serine (aspartate/glutamate) valine motifs. We have carried out a systematic study investigating in a heterologous expression system, the association of the four major NMDA receptor subtypes with the PSD-95 family of MAGUK proteins, chapsyn-110, PSD-95, synapse associated protein (SAP) 97 and SAP102. We report that although each PSD-95 MAGUK was shown to co-immunoprecipitate with NR1/NR2A, NR1/NR2B, NR1/NR2C and NR1/NR2D receptor subtypes, they elicited differential effects with regard to the enhancement of total NR2 subunit expression which then results in an increased cell surface expression of NMDA receptor subtypes. PSD-95 and chapsyn-110 enhanced NR2A and NR2B total expression which resulted in increased NR1/NR2A and NR1/NR2B receptor cell surface expression whereas SAP97 and SAP102 had no effect on total or cell surface expression of these subtypes. PSD-95, chapsyn-110, SAP97 and SAP102 had no effect on either total NR2C and NR2D subunit expression or cell surface NR1/NR2C and NR1/NR2D expression. A comparison of PSD-95alpha, PSD-95beta and PSD-95alpha(C3S,C5S) showed that PSD-95-enhanced cell surface expression of NR1/NR2A receptors was dependent upon the PSD-95 N-terminal C3,C5 cysteines. These observations support differential interaction of NMDA receptor subtypes with different PSD-95 MAGUK scaffolding proteins. This has implications for the stabilisation, turnover and compartmentalisation of NMDA receptor subtypes in neurones during development and in the mature brain.